Crossmodal correspondences: Assessing shape symbolism for cheese - Spence, C; Ngo, M; Percival, B; Smith, B (2013)
Several recent studies have demonstrated the existence of robust crossmodal correspondences between food and beverage items and shapes varying on the angular-round continuum. To date, however, the majority of this research has involved relatively simple gustatory, oral-somatosensory, and/or olfactory stimuli. In the present study, therefore, we extended this research in order to investigate whether people also exhibit robust crossmodal correspondences between shapes and cheese. To this end, participants in Experiment 1 (conducted at a Gastronomy event) tasted three aged farmhouse cheeses (Keen's Cheddar, Tunworth, and Berkswell, from Neal's Yard Dairy, UK). Participants rated each cheese using a single response scale anchored at either end by a rounded and an angular shape. Significant differences in shape symbolism were observed across the three cheeses. In Experiments 2 (conducted with cheesemongers and cheese experts) and 3 (conducted with customers in a cheese store), participants separately rated the olfactory, gustatory, and oral-somatosensory attributes of different cheeses (Tunworth, Lancashire, and Stawley) on the angular-round continuum. The results revealed that participants' crossmodal correspondences were based primarily on the taste, rather than the smell or texture of the cheeses. Implications of these findings for the marketing of dairy products are discussed. Practical applications: The results of the present study demonstrate that taste is the leading contributor to the systematic associations consumers have between the flavors of cheese and certain angular/sharp or organic/round shapes and speech sounds, with the same pattern of crossmodal correspondences being held across different tasting groups (non-experts, regular consumers, and cheesemongers/experts). These results provide insights regarding the abstract imagery that might best be associated with specific taste attributes in commercial cheeses. These results may also be used to not only develop abstract imagery for product packaging that can capture specific shape/sound symbolic properties, but also to develop descriptors that can provide a common ground on which to talk about cheeses, thereby improving communication between different panels of cheese tasters. © 2012 Elsevier Ltd.